Ramelteon administration enhances novel object recognition and spatial working memory in mice - Mikuru Kudara; Eriko Kato-Ishikura; Yuji Ikegaya; Nobuyoshi Matsumoto (Elsevier, 2023)
Ramelteon is used to ameliorate sleep disorders that negatively affect memory performance; however, it remains unknown whether ramelteon strengthens neutral memories, which do not involve reward or punishment. To address this, we monitored behavior of mice treated with vehicle/ramelteon while they performed a novel object recognition task and a spontaneous alternation task. Object memory performance in the novel object recognition task was improved only if ramelteon was injected before training, suggesting that ramelteon specifically enhances the acquisition of object recognition memory. Ramelteon also enhanced spatial working memory in the spontaneous alternation task. Altogether, acute ramelteon treatment enhances memory in quasi-natural contexts.